Parallel analysis and MBI-HSS: How many factors? - Merino Soto, Cesar; Angulo Ramos, Marisol (Colombia Medica, 2013)
It has been only recently possible to validate the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) among health professionals of Cali2, an important step for using this instrument with local empirical support in regard to its reliability of scoring and internal structure. However, two aspects of this analysis can be considered as methodological weaknesses. First, the Cronbach alpha coefficient was calculated for the total group of items, and this is absolutely inappropriate because: a)the authors did not demonstrate empirical support for accomplishing this (e.g., a hierarchical factor analysis), b) the literature indicates that factors in the MBI-HSS are generally independent, a characteristic also reported by Córdoba et al.